Teacher work motivation in the era of extrinsic incentives: Performance goals and pro-social commitments in the service of equity - Rick Mintrop; Miguel Ordenes (Arizona State University, 2017)
Mindful of the withering of high-stakes accountability and disappointing data from pay for performance evaluations in the US, we ask why management by extrinsic incentives and organizational goal setting may have been far less powerful than designers of accountability and extrinsic incentive systems had expected. We explore how system-generated motives (e.g., attaining specific organizational goals, preventing sanctions, or garnering rewards) stack up against autonomously generated, intrinsic, or service motives.? We found through both quantitative and qualitative data that for teachers in the charter schools a constellation of public service motives pre-dominated: diffuse pro-social commitments, ideologies of fairness and equity, a belief in the moral deservingness of deprived student populations in opposition to societal neglect, and identification with one's work as a personal calling. By comparison, monetary rewards were embraced as already deserved. Neither rewards, nor accountability, seemed to regulate behavior in a deep way. Prestige was not bestowed by official performance statuses within the accountability system, but flowed from judgments, personally communicated, by students, parents, or colleagues who had direct contact with teachers' work.